Method for producing solid electrolyte containing layer, method for producing solid battery, and solid battery

By combining the alkane-based compound with 5 or 6 carbon atoms in a solid battery and boron hydride compound, a solid electrolyte-containing layer is formed, which solves the problem of reduced ion conductivity after dissolution of the boron hydride compound and achieves better battery performance .

CN113871701BActive Publication Date: 2025-01-14TOYOTA JIDOSHA KK
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202110724675.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-30
Filing Date
2021-06-29
Publication Date
2025-01-14
Estimated Expiration
2041-06-29

AI Technical Summary

Technical Problem

In the prior art, when the boron hydride compound is dissolved in a solvent and precipitated, the ion conductivity is easily reduced, which affects the performance of the solid battery.

Method used

A solid electrolyte-containing layer is formed by combining an alkane-based compound containing 5 or 6 carbon atoms, and a boron hydride compound is removed during the drying process, thereby reducing the interaction between the boron hydride compound and the solvent, and reducing ion conductivity.

Benefits of technology

It effectively suppresses the reduction of the ion conductivity of the boron hydride compound, improves the uniformity of the solid electrolyte layer and the density of the electrode layer, and improves the performance of the solid battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113871701B_ABST
    Figure CN113871701B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for producing a solid electrolyte containing layer, a method for producing a solid battery, and a solid battery. The method for producing a solid electrolyte containing layer is a method for producing a solid electrolyte containing layer for a solid battery, and comprises the following steps: forming the solid electrolyte containing layer using a slurry containing a boron hydride compound and an alkane-based compound having 5 or 6 carbon atoms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for producing a solid electrolyte-containing layer, a method for producing a solid battery, and a solid battery. Background Art

[0002] A solid battery is a battery having a solid electrolyte layer between a positive electrode layer and a negative electrode layer, and has an advantage that safety devices can be easily simplified compared to a liquid battery having an electrolyte solution containing a flammable organic solvent.

[0003] As a solid electrolyte for solid batteries, boron hydride compounds are known. For example, in International Publication No. 2019 / 078130, a method for manufacturing an all-solid-state battery is disclosed, wherein a solution of a boron hydride compound dissolved in a solvent is applied or impregnated on at least one of a positive electrode layer and a negative electrode layer, and then the solvent is removed to precipitate the boron hydride compound. In addition, in Sangryun Kim et al., "A complex hydride lithium superionic conductor for high-energy-density all-solid-state lithium metal batteries", NATURE COMMUNICATIONS, (2019) 10: 1081, as a boron hydride compound, 0.7Li (CB9H 10 )-0.3Li(CB 11 H 12 ). Summary of the invention

[0004] In International Publication No. 2019 / 078130, a boron hydride compound is dissolved in a solvent, and then the solvent is removed to precipitate. If the boron hydride compound is dissolved in a solvent, the ion conductivity after precipitation may decrease.

[0005] The present disclosure provides a method for producing a solid electrolyte-containing layer, a method for producing a solid battery, and a solid battery capable of suppressing a decrease in the ion conductivity of a boron hydride compound.

[0006] A first embodiment of the present disclosure provides a method for producing a solid electrolyte containing layer, which is a method for producing a solid electrolyte containing layer for a solid battery, wherein the method comprises the following steps: forming the solid electrolyte containing layer using a slurry containing a boron hydride compound and an alkane compound having 5 or 6 carbon atoms.

[0007] According to the first aspect of the present disclosure, by combining the alkane compound with the boron hydride compound, it is possible to obtain a solid electrolyte-containing layer in which a decrease in the ion conductivity of the boron hydride compound is suppressed.

[0008] In the first embodiment disclosed above, the alkane-based compound may be a chain compound.

[0009] In the first embodiment disclosed above, the alkane-based compound may be a cyclic compound.

[0010] In the first aspect disclosed above, the alkane-based compound may contain at least one of pentane, cyclopentane and isohexane.

[0011] In the first aspect of the above disclosure, the solid electrolyte-containing layer may be a positive electrode layer.

[0012] In the first aspect of the above disclosure, the solid electrolyte-containing layer may be a negative electrode layer.

[0013] In the first aspect of the above disclosure, the solid electrolyte-containing layer may be a solid electrolyte layer.

[0014] In addition, the second scheme of the present disclosure provides a method for manufacturing a solid battery, which is a method for manufacturing a solid battery having a positive electrode layer, a negative electrode layer and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, wherein at least one layer among the positive electrode layer, the negative electrode layer and the solid electrolyte layer is a solid electrolyte containing layer containing a boron hydride compound, and the method comprises a step of manufacturing the solid electrolyte containing layer using the above-mentioned method for manufacturing the solid electrolyte containing layer.

[0015] According to the second scheme of the present disclosure, at least one of the positive electrode layer, the negative electrode layer and the solid electrolyte layer is a solid electrolyte containing layer containing a boron hydride compound, and the solid electrolyte containing layer is manufactured using the above-mentioned slurry containing an alkane-based compound, thereby obtaining a solid battery that suppresses the reduction in the ion conductivity of the boron hydride compound.

[0016] In addition, the third scheme of the present disclosure provides a solid battery, which is a solid battery having a positive electrode layer, a negative electrode layer and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, wherein at least one layer among the positive electrode layer, the negative electrode layer and the solid electrolyte layer is a solid electrolyte containing layer containing a boron hydride compound, and the solid electrolyte containing layer contains an alkane-based compound with a carbon number of 5 or 6 as a residual component.

[0017] According to the third scheme of the present disclosure, at least one of the positive electrode layer, the negative electrode layer and the solid electrolyte layer is a solid electrolyte containing layer containing a boron hydride compound, and further, the solid electrolyte containing layer contains the above-mentioned alkane compound as a residual component, thereby being able to make a solid battery that suppresses the reduction of the ion conductivity of the boron hydride compound.

[0018] In the third embodiment disclosed above, the alkane-based compound may be a chain compound.

[0019] In the third embodiment disclosed above, the alkane-based compound may be a cyclic compound.

[0020] In the third aspect disclosed above, the alkane-based compound may contain at least one of pentane, cyclopentane and isohexane.

[0021] In the third aspect of the above disclosure, the solid electrolyte-containing layer may be a positive electrode layer.

[0022] In the third aspect of the above disclosure, the solid electrolyte-containing layer may be a negative electrode layer.

[0023] In the third aspect of the above disclosure, the solid electrolyte-containing layer may be a solid electrolyte layer.

[0024] In the present disclosure, an effect is achieved in that a solid electrolyte-containing layer can be obtained in which a decrease in the ion conductivity of the boron hydride compound is suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Features, advantages, and technical and industrial significance of exemplary embodiments of the invention are described below with reference to the accompanying drawings, in which like reference numerals represent like elements, and in which:

[0026] Figure 1A This is a schematic cross-sectional view illustrating a method for producing a solid electrolyte-containing layer in the present disclosure.

[0027] Figure 1B This is a schematic cross-sectional view illustrating a method for producing a solid electrolyte-containing layer in the present disclosure.

[0028] Figure 1C This is a schematic cross-sectional view illustrating a method for producing a solid electrolyte-containing layer in the present disclosure.

[0029] Figure 2 This is a flow chart illustrating a method for manufacturing a solid state battery in the present disclosure.

[0030] Figure 3 This is a schematic cross-sectional view illustrating a solid state battery in the present disclosure. DETAILED DESCRIPTION

[0031] The present disclosure is described in detail below.

[0032] A. Method for producing a solid electrolyte containing layer

[0033] The method for producing a solid electrolyte-containing layer disclosed herein is a method for producing a solid electrolyte-containing layer for a solid battery, and comprises the steps of forming the solid electrolyte-containing layer using a slurry containing a boron hydride compound and an alkane-based compound having 5 or 6 carbon atoms.

[0034] Figures 1A to 1C This is a schematic cross-sectional view illustrating a method for manufacturing a solid electrolyte containing layer in the present disclosure, showing a case where the solid electrolyte containing layer is a positive electrode layer. First, a positive electrode current collector 4 ( Figure 1A ). Next, a slurry containing a positive electrode active material, a boron hydride compound and an alkane compound is applied on the positive electrode current collector 4 to form a coating layer 11 ( Figure 1B Then, the coating layer 11 is dried to remove the alkane compound, thereby forming the positive electrode layer 1 ( Figure 1C ).

[0035] According to the present disclosure, by combining an alkane-based compound with a boron hydride compound, a solid electrolyte containing layer that suppresses the reduction in ion conductivity of the boron hydride compound can be obtained. As described above, in International Publication No. 2019 / 078130, it is disclosed that a solution of a boron hydride compound dissolved in a solvent is applied or impregnated on at least one of a positive electrode layer and a negative electrode layer, and then the solvent is removed to precipitate the boron hydride compound.

[0036] On the other hand, if the boron hydride compound is dissolved in a solvent, the ion conductivity after precipitation is sometimes reduced. The reason is presumed to be as follows. That is, it is presumed that when the boron hydride compound is dissolved in a solvent, a strong interaction occurs between the anion component of the boron hydride compound and the solvent. As a result, it is presumed that even after precipitation, the ion conductivity of the boron hydride compound is reduced due to the influence of the solvent.

[0037] In the present disclosure, by combining an alkane compound with a boron hydride compound, a solid electrolyte containing layer that suppresses the reduction in the ionic conductivity of the boron hydride compound can be obtained. The reason is speculated as follows. That is, it is speculated that the alkane compound in the present disclosure does not dissolve the boron hydride compound or even if it dissolves, it is very little, so the interaction between the anionic component of the boron hydride compound and the solvent can be weakened. Furthermore, it is speculated that the large volume of the alkane compound is also a major factor in weakening the above-mentioned interaction. Therefore, it is speculated that the reduction in the ionic conductivity of the boron hydride compound can be suppressed after precipitation. In addition, for example, in the case of manufacturing an electrode layer (positive electrode layer or negative electrode layer) as a solid electrolyte containing layer, the alkane compound contained in the slurry can disperse the active material well, so an electrode layer with good uniformity can be obtained.

[0038] The solid electrolyte-containing layer in the present disclosure is not particularly limited as long as it is a layer containing a boron hydride compound as a solid electrolyte, and typical examples thereof include a positive electrode layer, a negative electrode layer, and a solid electrolyte layer.

[0039] 1. Case where the solid electrolyte containing layer is a positive electrode layer

[0040] In this case, the slurry for forming the positive electrode layer contains at least a positive electrode active material, a boron hydride compound, and an alkane-based compound. The slurry may further contain at least one of a conductive material and a binder as necessary.

[0041] (1) Solid Electrolyte

[0042] The slurry contains a boron hydride compound as a solid electrolyte. The boron hydride compound is usually present in a dispersed state in the slurry. In addition, the so-called boron hydride compound refers to a compound containing a cationic component and an anionic component having a BH bond. Examples of the cationic component include Li, Na, and K.

[0043] On the other hand, the anion component contains at least B and H. In addition, the anion component is usually a complex ion. The anion component may be a complex ion containing only B and H, or a complex ion containing C in addition to B and H. Examples of complex ions containing only B and H include BH4 - , B 10 H 10 2- , B 12 H 12 2- On the other hand, examples of complex ions containing B, H, and C include CB9H 10 - CB 11 H 12 - The boron hydride compound may have only one type of anion component or may have two or more types.

[0044] Examples of the boron hydride compound include LiCB 11 H 12 、LiCB9H 10 、Li2B 12 H 12 、Li2B 10 H 10 , LiBH4, and a composite compound formed by combining two or more of the above materials. The combination of the above materials can be selected arbitrarily. In particular, the boron hydride compound preferably has a structure consisting of xLiCB9H 10 ·(1-x)LiCB9H 10 The composition represented by (0<x<1) is because the ion conductivity is high. x may be 0.2 or more, 0.4 or more, or 0.6 or more. On the other hand, x may be 0.9 or less, or 0.8 or less.

[0045] The boron hydride compound may or may not contain iodine (I). Similarly, the boron hydride compound may or may not contain phosphorus (P). Similarly, the boron hydride compound may or may not contain sulfur (S).

[0046] Examples of boron hydride compounds containing I include compounds having a composition represented by xLiBH4·(1-x)LiI(0<x<1). x may be greater than or equal to 0.6 and less than or equal to 0.9. Examples of boron hydride compounds containing P and S include compounds having a composition represented by xLiBH4·(1-x)P2S5(0<x<1). x may be greater than or equal to 0.7 and less than or equal to 0.95. Examples of boron hydride compounds containing P and I include compounds having a composition represented by xLiBH4·(1-x)P2I4(0<x<1). x may be greater than or equal to 0.7 and less than or equal to 0.95. The slurry may contain only one boron hydride compound or may contain two or more.

[0047] The slurry may have only a boron hydride compound as a solid electrolyte, or may contain other materials. The proportion of the boron hydride compound relative to the solid electrolyte as a whole is, for example, 50% by weight or more, 70% by weight or more, or 90% by weight or more. In addition, the proportion of the solid electrolyte relative to the solid component of the slurry as a whole is, for example, 10% by weight or more, 20% by weight or more, or 30% by weight or more. On the other hand, the above-mentioned proportion of the solid electrolyte is, for example, 70% by weight or less, or 60% by weight or less.

[0048] (2) Dispersion medium

[0049] The slurry contains an alkane compound having 5 or 6 carbon atoms as a dispersion medium. The so-called "alkane compound having 5 or 6 carbon atoms" refers to a compound having a general formula C n H 2n+2 (n is 5 or 6) represented by a chain saturated hydrocarbon, represented by the general formula C n H 2n (n is 5 or 6) and their derivatives.

[0050] The alkane compound may be a chain compound or a cyclic compound. Examples of chain compounds (chain alkane compounds) include pentane (normal pentane), isopentane (2-methylbutane), hexane (normal hexane), isohexane (2-methylpentane), 3-methylpentane, diisopropyl (2,3-dimethylbutane), and neohexane (2,2-dimethylbutane). On the other hand, examples of cyclic compounds (cyclic alkane compounds) include cyclopentane, cyclohexane, and methylcyclopentane. In addition, the carbon chain in the alkane compound may or may not have a branched structure.

[0051] In particular, the alkane compound is preferably pentane, cyclopentane or isohexane. This is because the reduction in the ionic conductivity of the boron hydride compound can be suppressed. The slurry may contain only one alkane compound having 5 or 6 carbon atoms, or may contain two or more. In addition, a chain alkane compound and a cyclic alkane compound may be used in combination. In addition, the relative dielectric constant (25°C) of the alkane compound is preferably, for example, less than 2. In addition, the vapor pressure (25°C) of the alkane compound is preferably, for example, more than 20 kPa.

[0052] The slurry may contain only an alkane compound having 5 or 6 carbon atoms as a dispersion medium, or may contain other materials. The proportion of the alkane compound having 5 or 6 carbon atoms relative to the entire dispersion medium is, for example, 50% by weight or more, 70% by weight or more, or 90% by weight or more. The solid content concentration of the slurry is, for example, 30% by weight or more, 40% by weight or more, or 50% by weight or more. On the other hand, the solid content concentration of the slurry is, for example, 80% by weight or less, or 70% by weight or less.

[0053] (3) Positive electrode active material

[0054] The positive electrode active material is not particularly limited, and typical examples include oxide active materials and elemental sulfur. Examples of oxide active materials include LiCoO2, LiMnO2, LiNiO2, LiVO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and other rock salt layered active materials, LiMn2O4, Li(Ni 0.5 Mn 1.5 )O4 and other spinel active materials, LiFePO4, LiMnPO4, LiNiPO4, LiCuPO4 and other olivine active materials.

[0055] The shape of the positive electrode active material may be, for example, a particle shape. The average particle size (D 50 ) is, for example, 0.1 μm or more and 50 μm or less. It should be noted that the average particle size can be calculated, for example, by measurement using a laser diffraction particle size distribution meter or a scanning electron microscope (SEM). The proportion of the positive electrode active material relative to the entire solid content of the slurry is, for example, 50% by weight or more, and can be 60% by weight or more. On the other hand, the above-mentioned proportion of the positive electrode active material is, for example, 80% by weight or less.

[0056] (4) Slurry

[0057] The slurry may contain a conductive material. By adding a conductive material, the electronic conductivity of the solid electrolyte containing layer is improved. As the conductive material, for example, acetylene black, Ketjen black, and carbon fiber can be listed. In addition, the slurry may contain a binder. By adding a binder, the compactness of the solid electrolyte containing layer is improved. As the binder, for example, fluorine-based binders such as PVDF-based binders, rubber-based binders, and acrylic binders can be listed. In addition, the slurry may contain additives such as thickening materials and dispersing materials as needed.

[0058] As a method for preparing the slurry, for example, a method of kneading a positive electrode active material, a boron hydride compound and an alkane compound can be cited. As a kneading method, for example, an ultrasonic homogenizer, a vibrator, a thin film gyratory mixer, a dissolver, a homogeneous mixer, a kneader, a roll mill, a sand mill, an attritor, a ball mill, a vibration mill, and a high-speed impeller mill can be cited.

[0059] (5) Method for forming positive electrode layer

[0060] As a method for forming the positive electrode layer, for example, a method of coating the slurry on the substrate to form a coating layer and a method of drying the coating layer to form a positive electrode layer can be listed. As a coating method for the slurry, for example, a doctor blade method, a die coating method, a gravure coating method, a spray coating method, an electrostatic coating method, and a rod coating method can be listed.

[0061] The substrate on which the slurry is applied is not particularly limited, and examples thereof include a positive electrode collector. By applying the slurry on the positive electrode collector, a positive electrode having good adhesion between the positive electrode collector and the positive electrode layer can be obtained. Examples of materials for the positive electrode collector include SUS, aluminum, nickel, iron, titanium, and carbon.

[0062] There is no particular limitation on the method for drying the coating layer, and general methods such as warm air drying, infrared drying, reduced pressure drying, and induction heating drying can be listed. In addition, as the drying atmosphere, for example, inert gas atmospheres such as Ar gas atmosphere and nitrogen atmosphere, atmospheric atmosphere, and vacuum can be listed. In particular, the method for drying the coating layer is preferably heated vacuum drying. There is no particular limitation on the drying temperature, and it is preferably a temperature at which the material contained in the coating layer does not deteriorate. After the coating layer is dried, a pressing treatment can be performed as needed. As a pressing treatment, for example, a pressing treatment for densifying the positive electrode layer can be listed.

[0063] The thickness of the positive electrode layer is, for example, 0.1 μm or more. On the other hand, the thickness of the positive electrode layer is, for example, 1000 μm or less, and may be 300 μm or less.

[0064] 2. Case where the solid electrolyte containing layer is a negative electrode layer

[0065] In this case, the slurry for forming the negative electrode layer contains at least a negative electrode active material, a boron hydride compound, and an alkane-based compound, and may further contain at least one of a conductive material and a binder as necessary.

[0066] The negative electrode active material is not particularly limited, and examples thereof include carbon active materials, metal active materials, and oxide active materials. Examples of carbon active materials include graphite, hard carbon, and soft carbon. On the other hand, examples of metal active materials include simple substances such as Li, Si, In, Al, and Sn, and alloys containing at least one of these elements. In addition, examples of oxide active materials include SiO, Li4Ti5O 12 The shape of the negative electrode active material may be, for example, a particle shape. The average particle size (D 50 ) is, for example, 0.1 μm or more and 50 μm or less. The proportion of the negative electrode active material relative to the entire solid content of the slurry is, for example, 30 wt % or more, and can be 50 wt % or more. On the other hand, the above proportion of the negative electrode active material is, for example, 80 wt % or less.

[0067] Other matters related to the boron hydride compound, alkane compound, conductive material, binder and slurry are basically the same as those described in the above-mentioned "1. When the solid electrolyte containing layer is a positive electrode layer", and therefore the description here is omitted.

[0068] As a method for forming a negative electrode layer, for example, a method including coating a slurry on a substrate to form a coating layer and drying the coating layer to form a negative electrode layer can be listed. Except for using a negative electrode active material instead of a positive electrode active material, it is basically the same as the content described in the above "1. The solid electrolyte containing layer is a positive electrode layer", so the description here is omitted. In addition, when the substrate to which the slurry is applied is a negative electrode collector, the material of the negative electrode collector can be, for example, SUS, copper, nickel, and carbon.

[0069] The thickness of the negative electrode layer is, for example, 0.1 μm or more. On the other hand, the thickness of the negative electrode layer is, for example, 1000 μm or less, and may be 300 μm or less.

[0070] 3. Case where the solid electrolyte containing layer is a solid electrolyte layer

[0071] In this case, the slurry for forming the solid electrolyte layer (separator layer) contains at least a boron hydride compound and an alkane-based compound, and may further contain a binder as necessary.

[0072] Other matters related to the boron hydride compound, alkane compound, binder and slurry are basically the same as those described in the above "1. When the solid electrolyte containing layer is a positive electrode layer", so the description here is omitted. The ratio of the solid electrolyte to the entire solid content of the slurry is, for example, 80% by weight or more, 90% by weight or more, and 95% by weight or more.

[0073] As a method for forming a solid electrolyte layer, for example, a method having a coating process of coating a slurry on a substrate to form a coating layer and a drying process of drying the coating layer to form a solid electrolyte layer can be cited. Except that no positive electrode active material and conductive material are used, it is basically the same as the content described in the above "1. The case where the solid electrolyte containing layer is a positive electrode layer", so the description here is omitted. As a substrate for coating the slurry, for example, at least one of a positive electrode layer and a negative electrode layer can be listed. In addition, as a substrate, a transfer substrate can be used. In this case, it is preferred to form a solid electrolyte layer on a transfer substrate, and after the obtained solid electrolyte layer is in contact with the positive electrode layer or the negative electrode layer, the transfer substrate is peeled off.

[0074] The thickness of the solid electrolyte layer is, for example, 0.1 μm or more. On the other hand, the thickness of the solid electrolyte layer is, for example, 1000 μm or less, and may be 300 μm or less.

[0075] B. Method for manufacturing solid state battery

[0076] Figure 2 This is a flow chart illustrating a method for manufacturing a solid state battery in the present disclosure. Figure 2 The method for manufacturing a solid battery shown in has: a positive electrode layer forming step for forming a positive electrode layer, a negative electrode layer forming step for forming a negative electrode layer, and a solid electrolyte layer forming step for forming a solid electrolyte layer. In the present disclosure, at least one of the positive electrode layer, the negative electrode layer, and the solid electrolyte layer is a solid electrolyte containing layer containing a boron hydride compound, and the solid electrolyte containing layer is manufactured by the method described in the above-mentioned "A. Method for manufacturing a solid electrolyte containing layer".

[0077] According to the present disclosure, at least one of the positive electrode layer, the negative electrode layer and the solid electrolyte layer is a solid electrolyte containing layer containing a boron hydride compound, and further, the solid electrolyte containing layer is manufactured using the above-mentioned slurry containing an alkane-based compound, thereby obtaining a solid battery that suppresses the reduction in the ion conductivity of the boron hydride compound.

[0078] In the present disclosure, any one of the positive electrode layer, the negative electrode layer, and the solid electrolyte layer may be a solid electrolyte containing layer, two of the positive electrode layer, the negative electrode layer, and the solid electrolyte layer may be solid electrolyte containing layers (the two layers may be selected in any combination), and all of the positive electrode layer, the negative electrode layer, and the solid electrolyte layer may be solid electrolyte containing layers. The method for manufacturing the solid electrolyte containing layer is the same as that described in the above-mentioned "A. Method for manufacturing the solid electrolyte containing layer", so the description here is omitted.

[0079] The manufacturing method of the solid battery in the present disclosure may have a stacking process of stacking the positive electrode layer, the solid electrolyte layer and the negative electrode layer in sequence to form a power generation element in addition to the above-mentioned steps (positive electrode layer formation step, negative electrode layer formation step and solid electrolyte layer formation step). There is no particular limitation on the stacking method, and any method can be used. In addition, the power generation element can be pressed as needed. The characteristics of the obtained solid battery will be described in "C. Solid Battery" described later.

[0080] C. Solid state battery

[0081] Figure 3 This is a schematic cross-sectional view illustrating a solid state battery in the present disclosure. Figure 3 The solid battery 10 shown in the figure has a positive electrode layer 1, a negative electrode layer 2, a solid electrolyte layer 3 formed between the positive electrode layer 1 and the negative electrode layer 2, a positive electrode collector 4 for collecting current from the positive electrode layer 1, a negative electrode collector 5 for collecting current from the negative electrode layer 2, and a battery case 6 for accommodating these components. At least one of the positive electrode layer 1, the negative electrode layer 2, and the solid electrolyte layer 3 is a solid electrolyte containing layer containing a boron hydride compound. Furthermore, the solid electrolyte containing layer contains an alkane-based compound having 5 or 6 carbon atoms as a residual component.

[0082] According to the present disclosure, at least one of the positive electrode layer, the negative electrode layer and the solid electrolyte layer is a solid electrolyte containing layer containing a boron hydride compound, and the solid electrolyte containing layer contains the above-mentioned alkane compound as a residual component, so that a solid battery that suppresses the reduction of the ion conductivity of the boron hydride compound can be prepared. In other words, by using the above-mentioned slurry containing an alkane compound to manufacture a solid electrolyte containing layer, a solid battery that suppresses the reduction of the ion conductivity of the boron hydride compound can be prepared.

[0083] The residual component in the present disclosure is the dispersion medium remaining when the solid electrolyte containing layer is formed using the above-mentioned slurry containing alkane-based compounds. The presence of the residual component can be confirmed, for example, by heating the sample and measuring the released gas by gas chromatography. From the perspective of battery performance, the amount of the residual component contained in the layer is preferably small. The amount of the residual component is, for example, less than 20000 ppm, and can be less than 10000 ppm. On the other hand, the lower limit of the amount of the residual component can be higher than the detection limit. This is because the side reactions caused by the residual component can be suppressed.

[0084] In the present disclosure, any one of the positive electrode layer, the negative electrode layer and the solid electrolyte layer may be a solid electrolyte containing layer, two of the positive electrode layer, the negative electrode layer and the solid electrolyte layer may be solid electrolyte containing layers (the two layers can be selected in any combination), and all of the positive electrode layer, the negative electrode layer and the solid electrolyte layer may be solid electrolyte containing layers.

[0085] The solid battery in the present disclosure generally has a positive electrode layer, a negative electrode layer and a solid electrolyte layer. For these layers, the contents described in the above-mentioned "A. Method for producing a solid electrolyte containing layer" are the same, so the description here is omitted. In addition, the solid battery is preferably a lithium ion battery. The solid battery can be a primary battery or a secondary battery, preferably a secondary battery. This is because it can be repeatedly charged and discharged, for example, it can be used as a vehicle-mounted battery. As the shape of the solid battery, for example, a coin type, a laminate type, a cylindrical type, and a square type can be listed.

[0086] The present disclosure is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative only, and any solution having substantially the same configuration and achieving the same function and effect as the technical concept described in the claims of the present disclosure is included in the technical scope of the present disclosure.

[0087] [Experimental Example 1]

[0088] (Synthesis of solid electrolyte)

[0089] LiCB9H 10 H2O (Katchem) and LiCB 11 H 12 0.5H2O (Katchem) was vacuum dried at 160°C for 12 hours. The two dried powders were weighed to obtain LiCB9H 10 :LiCB 11 H 12=7:3 molar ratio, and mixed in a mortar for 15 minutes. The obtained mixture was added to a zirconia pot, and crushing balls were also added. The pot was sealed and placed in a planetary ball mill, and mechanical grinding was performed at 400 rpm for 20 hours. Then, mixed in a mortar for 15 minutes to obtain a borohydride compound (solid electrolyte).

[0090] (Preparation of solid electrolyte for evaluation)

[0091] The obtained solid electrolyte was immersed in pentane, dispersed with a homogenizer for 30 seconds, and rested for 10 seconds. This cycle was performed 10 times. Then, the state of the solid electrolyte was visually confirmed to confirm that the solid electrolyte remained as particles in pentane. Then, a dispersion (a mixture of solid electrolyte and pentane) was added to a glass dish and dried on a hot plate at 100°C for 1 hour to obtain a solid electrolyte for evaluation.

[0092] [Experimental Examples 2 to 5 and Comparative Experimental Examples 1 to 3]

[0093] A solid electrolyte for evaluation was obtained in the same manner as in Experimental Example 1, except that cyclopentane (Experimental Example 2), isohexane (Experimental Example 3), hexane (Experimental Example 4), cyclohexane (Experimental Example 5), heptane (Comparative Experimental Example 1), butyl butyrate (Comparative Experimental Example 2), and N-methyl-2-pyrrolidone (Comparative Experimental Example 3) were used instead of pentane.

[0094] [evaluate]

[0095] For the solid electrolytes used for evaluation obtained in Experimental Examples 1 to 5 and Comparative Experimental Examples 1 to 3, a voltage of ±10mV was applied and the resistance value was measured in the range of 0.01Hz to 1MHz. The ion conductivity was calculated using the measured resistance value and the thickness of the solid electrolyte. In addition, the ion conductivity was calculated in the same way using the solid electrolyte before immersion in the liquid, and the maintenance rate of the ion conductivity was found. The results are shown in Table 1. Maintenance rate of ion conductivity (%) = (ion conductivity after immersion) / (ion conductivity before immersion) × 100

[0096]

Table 1

[0097]

[0098] As shown in Table 1, in Experimental Examples 1 to 5, the maintenance rate of ion conductivity is higher than that in Comparative Experimental Examples 1 to 3. In particular, in Experimental Examples 1 to 3, the maintenance rate of ion conductivity is particularly good. The reason is not completely clear, but it is speculated that the alkane compounds used in Experimental Examples 1 to 3 have high vapor pressures, so the alkane compounds are easily removed by drying. In this way, it was confirmed that the use of alkane compounds can suppress the decrease in ion conductivity of the boron hydride compound.

[0099] On the other hand, in Comparative Experimental Example 1, heptane was used as an alkane, but the ion conductivity maintenance rate was low. The reason is not completely clear, but the following possibility is assumed: the vapor pressure of heptane is lower than the vapor pressure of the alkane-based compounds used in Experimental Examples 1 to 5, so heptane is not sufficiently removed by drying. In addition, the following possibility is also assumed: heptane changes the structure of the boron hydride compound (solid electrolyte).

[0100] [Experimental Examples 6 to 10]

[0101] Solid electrolytes for evaluation were obtained in the same manner as in Experimental Examples 1 to 5, except that vacuum drying at 100° C. was performed instead of drying using a hot plate at 100° C.

[0102] [evaluate]

[0103] The ion conductivity maintenance rate was determined in the same manner as above using the solid electrolytes for evaluation obtained in Experimental Examples 6 to 10. The results are shown in Table 2.

[0104]

Table 2

[0105]

[0106] Comparing Table 2 with Table 1 above, the ion conductivity maintenance rates of Experimental Examples 6 to 10 are higher than those of Experimental Examples 1 to 5. This suggests that it is preferable to have a smaller amount of alkane compounds remaining in the solid electrolyte. In particular, in Experimental Example 6, the ion conductivity exceeds 100%. It is speculated that the reason is that the vapor pressure of pentane is particularly high, and further, the affinity with water is also high, so the water remaining in the solid electrolyte also volatilizes together with heptane.

Claims

1. A method for producing a solid electrolyte containing layer, which is a method for producing a solid electrolyte containing layer for a solid battery, wherein: The process includes: using a 10 H2O and LiCB 11 H 12 The solid electrolyte containing layer is formed by mixing a slurry of a boron hydride compound obtained by mixing 0.5H2O and an alkane compound having 5 or 6 carbon atoms.

2. The method according to claim 1, wherein: The alkane-based compound is a chain compound.

3. The method according to claim 1, wherein: The alkane-based compound is a cyclic compound.

4. The method according to claim 1, wherein: The alkane compound contains at least one of pentane, cyclopentane and isohexane.

5. The method according to any one of claims 1 to 4, wherein The solid electrolyte containing layer is a positive electrode layer.

6. The method according to any one of claims 1 to 4, wherein The solid electrolyte containing layer is a negative electrode layer.

7. The method according to any one of claims 1 to 4, wherein The solid electrolyte containing layer is a solid electrolyte layer.

8. A method for manufacturing a solid battery, comprising: a method for manufacturing a solid battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, wherein: At least one of the positive electrode layer, the negative electrode layer and the solid electrolyte layer is a solid electrolyte containing layer containing a boron hydride compound, The method comprises the step of manufacturing the solid electrolyte-containing layer by using the method for manufacturing a solid electrolyte-containing layer according to any one of claims 1 to 7.

9. A solid battery comprising a positive electrode layer, a negative electrode layer and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, wherein: At least one of the positive electrode layer, the negative electrode layer and the solid electrolyte layer contains LiCB9H 10 H2O and LiCB 11 H 12 The solid electrolyte containing layer of the boron hydride compound obtained by 0.5H2O is formed by dissolving the boron hydride compound in an alkane compound having 5 or 6 carbon atoms to prepare a slurry, and using the slurry to form the solid electrolyte containing layer.

10. The solid battery according to claim 9, wherein: The alkane-based compound is a chain compound.

11. The solid battery according to claim 9, wherein: The alkane-based compound is a cyclic compound.

12. The solid battery according to claim 9, wherein: The alkane compound contains at least one of pentane, cyclopentane and isohexane.

13. The solid battery according to any one of claims 9 to 12, wherein The solid electrolyte containing layer is a positive electrode layer.

14. The solid battery according to any one of claims 9 to 12, wherein The solid electrolyte containing layer is a negative electrode layer.

15. The solid battery according to any one of claims 9 to 12, wherein The solid electrolyte containing layer is a solid electrolyte layer.

Citation Information

Patent Citations

  • Production method for all-solid-state battery

    WO2019078130A1

  • Positive-electrode mixture, manufacturing method therefor, and all-solid-state lithium-sulfur battery

    US20160254529A1

  • Method of Manufacturing Sulfide-Based Solid Electrolyte Through Wet Process

    US20180138544A1